Quasi-dimensional, multi-zone combustion modelling of turbulent entrainment and flame stretch for a spark ignition engine fuelled with hydrogen-enriched biogas. (16th April 2009) - Rakopoulos, C.D.; Michos, C.N.
A quasi-dimensional, multi-zone combustion model for spark ignition (SI) engines is analytically presented. The model is incorporated into a closed cycle simulation code for the prediction of performance and nitric oxide (NO) emissions of a SI engine operated on biogas, with small amounts of hydrogen added. The burning process is handled based on the combination of turbulent entrainment theory and flame stretch concepts. An expression of the turbulent burning velocity of a flamelet model is adopted for simulating the entrainment speed into the flame zone. A model of flame stretch is also used, in order to assess the flame response on combined effects of curvature, turbulent strain and preferential diffusion. In addition, the burned gas behind the flame is treated using a multi-zone thermodynamic formulation. In this way, the temperature and chemical species concentration gradients of the burned mixture can be captured, which are very important for accurate NO emissions predictions. After calibration of the model, illustrative diagrams are presented concerning the effect of hydrogen addition in biogas on burning rates, characteristic speeds, mass diffusivity of fuel and flame propagation. Furthermore, zone-resolved thermodynamic and geometric characteristics are given for the multiple burned zones. Finally, predictions of NO emissions are compared with the respective measured values.